Teacher of Orators by Lucian: compositional techniques and contamination of genres (Minerva, 2023)
This paper aims to analyse both the refined devices of literary contamination and the textual techniques that permeate Teacher of Orators by Lucian of Samosata, a pamphlet which attacks the lack of moderation of certain fashionable members of the Second Sophistic. Besides evaluating Lucian’s criticism in an impartial way, this paper offers an analysis of the relationship among the dialogue itself and other literary genres, such as theatre and the contemporary Sophistic declamations. Furthermore, the present study explores the parodic nature of the work and focuses on investigating the overlapping in the different levels of meaning, as typical of parodic operation.
Keywords: Second Sophistic; Lucian of Samosata; Teacher of Orators; Sophistic declamations and theatrical influences; literary contamination